Millennial travelers decision making influenced through user-generated contents and psychological attributes on destination loyalty to a tropical island - Jamaludin, Mazlina; Aziz, Azlizam; Mariapan, Manohar (Global Academic Excellence (M), 2018)
An investigation into the decision-making process of millennial travelers influenced by, using user-generated contents, and other psychological factors such as pull motivation, cognitive image on destination loyalty, took place at a small tropical Island in Malaysia called Pangkor. A total of 170 respondents were selected using purpusive sampling. Social cognitive theory was used to describe the phenomenon of this research. Results revealed that user-generated contents had a significant relationship on push motivation and explained 11.3% of the variance in push motivation. Push motivation had a significant relationship, but with a low influence, with destination loyalty, it had a high significant relationship with cognitive image. Meanwhile, cognitive image had a significant relationship with destination loyalty. Cognitive image and pull motivation play important roles in explaining 46.3% of the variance in destination loyalty, while push motivation alone explains 52.2% of variance in cognitive image. These findings indicate that cognitive image plays the most important role in the millennial travelers’ decision making process to visit an isolated tropical island. This proves that millennial travelers use user-generated contents as an information source for guidance rather than solely using it for making decisions.